Dampak Kualitas dan Harga Terhadap Keputusan Pembelian Kaca di Surabaya: Dampak Kualitas dan Harga Terhadap Keputusan Pembelian Kaca di Surabaya - maharani, devyana riska; kusmayati, nindya kartika; Wulansari, Dhyah; devyana, devyana riska maharani (RISK : Jurnal Riset Bisnis dan Ekonomi, 2023)
This research aims to determine whether quality and price can influence glass purchasing decisions in Surabaya. The population is taken from residents in the Surabaya area who use glass. At the same time, a sample of 40 people was used as respondents with quantitative methods using a correlational approach. The use of questions by distributing them to respondents is a data collection technique used in this study. The data analysis technique used multiple near regression, which previously tested the validity and reliability to prevent the data from being biased. Multiple regression linear test results of Y = 6.317 + 0.397X1 + 0.424X2 + e Hypothesis testing using partial t-test and simultaneous f-test. The results of this study are that quality and price have a positive and significant effect on the purchase of glass in the Surabaya area. This is because the price of glass in the Surabaya area is considered relatively cheap and has a major influence on purchasing decisions. It's even better quality.